From historical movements to educational reform: the role of the work-study movement in France in the development of vocational education in China - Luo, Guanqun (Frontiers in Education, 2025)
IntroductionThis study examines how the French Work-Study Movement influenced the early development of vocational education in China. While current research tends to emphasize Anglo-American and Japanese models, this paper highlights the pivotal role of the French vocational education system in shaping China’s early modernization efforts and demonstrates how transnational educational practices were localized to meet national needs.MethodsGrounded in Bourdieu’s theory of education and social reproduction, the study employs qualitative historical methods, including analysis of primary documents such as letters, memoirs, and policy records, as well as comparative analysis between the French and Chinese vocational education systems of the early 20th century.ResultsFindings reveal that the Work-Study Movement in France provided a practical model that integrated theoretical learning with industrial labor, which Chinese students experienced firsthand. These experiences not only helped shape China’s early vocational education system but also challenged traditional cultural attitudes that devalued manual labor.DiscussionThe study concludes that the work-study model served as a key mechanism for the localization of Western vocational education in China. It emphasizes the model’s historical relevance and its ongoing value as a framework for integrating education with industry in contemporary educational reform.